Pengaruh Adopsi Artificial Intelligence terhadap Kinerja Keuangan UMKM di Indonesia - Ernawati, Ernawati (Institut Teknologi dan Bisnis (ITB) Semarang, 2026)
The rapid development of Artificial Intelligence (AI) has accelerated the transformation of financial management practices, particularly among Micro, Small, and Medium Enterprises (MSMEs). However, empirical studies examining the impact of AI adoption on MSMEs' financial performance remain limited, especially those exploring the mediating role of financial decision-making. This study aims to analyze the effect of Artificial Intelligence adoption on the financial performance of MSMEs by positioning financial decision-making as a mediating variable. A quantitative research approach was employed using a survey method involving MSME owners who have adopted digital technologies in their business operations. Primary data were collected through structured questionnaires and analyzed using Structural Equation Modeling Partial Least Squares (SEM-PLS). The proposed research model hypothesizes that AI adoption positively influences the quality of financial decision-making, which subsequently enhances MSMEs' financial performance. The novelty of this study lies in the development of an integrated empirical model linking AI adoption, financial decision-making, and financial performance within the MSME context. The findings are expected to enrich the literature on digital financial management while providing practical insights for MSME practitioners and policymakers in designing strategies to optimize AI utilization for improving financial management effectiveness and strengthening business competitiveness in the digital economy.